Pengaruh Beban Kerja, Insentif dan Jam Kerja terhadap Kinerja Karyawan pada Kumon Puskopad - Pradana, Bagas Ardi; Susanti, Ety Dwi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the Effect of Workload, Incentives, and Working Hours on the Performance of Kumon Puskopad Employees. Probability sampling is the method used for sampling. There were 20 people who participated in this study's sample. The Statistical Product and Service Solutions (SPSS) Version 29 Program was used for the multiple linear regression analysis that was used in this study. Workload, incentives, and working hours all have a significant impact on employee performance, as demonstrated by the research, as does partial workload, which has a positive and significant impact on on Kumon Puskopad Employee Performance. Meanwhile, incentives and working hours have no significant effect on the performance of Kumon Puskopad employees. Companies need to pay attention to Workload, Incentives, and Working Hours which will improve the Performance of Kumon Puskopad Employees.